Relationships between beliefs about statins and non-adherence in inpatients from Northwestern China: a cross-sectional survey - Li, Haiyan; Jia, Xiaoni; Min, Hui; Zhang, Yingli; Wang, Huichuan; Zhai, Yuyao (Frontiers in Pharmacology, 2023)
Background: Studies have identified patients’ beliefs about medicines as an important determinant of non-adherence. However, scant data are available on the possible association between patients’ beliefs and statin non-adherence among adult patients in China. The objectives of this study are to assess the prevalence of statin non-adherence, and to identify the factors associated with statin non-adherence, especially the association between inpatients’ beliefs about statins and non-adherence in a tertiary hospital in the Northwestern China. Methods: A cross-sectional questionnaire-based survey was carried out in the department of cardiology and neurology between February and June 2022. The Beliefs about Medicine Questionnaire (BMQ) was used to assess patients’ beliefs about statins. The Adherence to Refills and Medications Scale (ARMS) was used to assess statin adherence. Logistic regression analyses were performed to identify the factors associated with statin non-adherence. Receiver operator characteristic (ROC) was conducted to assess the performance of the logistic regression model in predicting statin non-adherence. Results: A total of 524 inpatients participated and finished the questionnaire, 426 (81.3%) inpatients were non-adherent to statin, and 229 (43.7%) inpatients expressed strong beliefs about the stain treatment necessity, while 246 (47.0%) inpatients expressed strong concerns about the potential negative effects. We found that the low necessity beliefs about statin (adjusted odds ratio [OR] and 95% confidence interval [CI], 1.607 [1.019, 2.532]; p = 0.041), prescribed rosuvastatin (adjusted OR 1.820 [1.124, 2.948]; p = 0.015) and ex-drinker (adjusted OR 0.254 [0.104, 0.620]; p = 0.003) were independent determinants of statin non-adherence. Conclusion: Statin adherence was poor in this study. The findings indicated a significant association between inpatients’ lower necessity beliefs and statin non-adherence. More attention should be focused on statin non-adherence in China. Nurses and pharmacists could play an important role in patient education and patient counseling in order to improve medication adherence.